Nonaggregated alpha-Synuclein Influences SNARE-Dependent Vesicle Docking via Membrane Binding - Lai, Ying; Kim, Sunae; Varkey, Jobin; Lou, Xiaochu; Song, Jae-Kyun; Diao, Jiajie; Langen, Ralf; Shin, Yeon-Kyun (AMER CHEMICAL SOC, 2014)
alpha-Synuclein (alpha-Syn), a major component of Lewy body that is considered as the hallmark of Parkinson's disease (PD), has been implicated in neuroexocytosis. Overexpression of alpha-Syn decreases the neurotransmitter release. However, the mechanism by which alpha-Syn buildup inhibits the neurotransmitter release is still unclear. Here, we investigated the effect of nonaggregated alpha-Syn on SNARE-dependent liposome fusion using fluorescence methods. In ensemble in vitro assays, alpha-Syn reduces lipid mixing mediated by SNAREs. Furthermore, with the more advanced single-vesicle assay that can distinguish vesicle docking from fusion, we found that alpha-Syn specifically inhibits vesicle docking, without interfering with the fusion. The inhibition in vesicle docking requires alpha-Syn binding to acidic lipid containing membranes. Thus, these results imply the existence of at least two mechanisms of inhibition of SNARE-dependent membrane fusion: at high concentrations, nonaggregated alpha-Syn inhibits docking by binding acidic lipids but not v-SNARE; on the other hand, at much lower concentrations, large alpha-Syn oligomers inhibit via a mechanism that requires v-SNARE interaction [Choi et al. Proc. Natl. Acad. Sci. U. S. A. 2013, 110 (10), 4087-4092].
Keywords: SYNAPTIC PLASTICITY; SINGLE-MOLECULE; FUSION; COMPLEX; DRIVEN; CA2+; OVEREXPRESSION; RELEASE; CELLS; STEP